Two cases of complete hydatidiform mole and coexistent live fetus - Vimercati, Antonella (CIC Edizioni Internazionali, 2013)
The aim of this study was to report the clinical features, management, and outcome of complete hydatidiform mole with a coexisting viable fetus. Two cases are reported. In both cases ultrasound examination demonstrated a normally growing live fetus alongside a normal placenta and an additional intrauterine echogenic mass with features of hydatidiform mole. The hCG levels were significantly increased and fetal karyotypes were normal. A cesarean section performed at 28 weeks’ gestation in the first case and at 26 weeks’ gestation in the second one resulted in the delivery of live normal infant and two adjoining placentas in both cases. Microscopic examination of the abnormal placentas confirmed complete hydatidiform mole. The babies did well and serial maternal serum hCG levels showed a declining trend and were undetectable by a few months after delivery. Continuation of a twin pregnancy with complete hydatidiform mole (CHMF) is an acceptable option. There is, although, an increased risk of developing maternal and fetal complications. Close surveillance of an ongoing pregnancy is compulsory to detect potential early signs of complications.